TREATMENT OF AMITRAZ TOXICITY IN A DOG: A CASE REPORT - B.K. Bhagya; V. Shivakumar; M. Shivakumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A one and half year, female, non descriptive dog was presented to Veterinary College Hospital, Hassan with the history of incoordination, drowsiness and vomiting after accidental oral administration ofAmitraz liquid (RIDD®) by the owner. On physical examination animal was dull and depressed. Sedation (drowsiness) and hypothermia was noticed with the rectal temperature of 98.8°E Hemato-biochemical findings were within the normal range. Based on history and clinical signs, the case was diagnosed as amitrazpoisoning and animal was treated with Yohimbine Hydrochloride at the rate of 0.2 mg per Kg body weight intramuscularly and activated charcoal per orally, along with the supportive therapy. Animal was completely recovered after 5 days of treatment.